Employment Effects of Growth Rebalancing in China. (IMF Working Papers; Working Paper ;, 2009)
This paper gauges the potential effects on employment of rebalancing China's exportoriented growth model toward domestic demand, particularly private consumption. Shifting to a private consumption-led growth likely means more demand for existing and new services as well as reorienting the production of tradable goods toward domestic markets. In China's case, this would also imply moving a large number of less skilled labor from the tradable sector to the nontradable sector. The paper shows that while rebalancing China's growth toward a domestic-demand-led economy would likely raise aggregate employment and employment opportunities in the longer term, there could be employment losses in the short run as the economy moves away from the tradable sector toward the nontradable sector. Mitigating these costs will require active labor market policies to cushion the employment impact in the transition, particularly in meeting the skills gap of associated with this transition.